Prediction of manufacturing flexibility by the use of simulation modelling - Matupi, Newton B. (Cranfield University, 1997)
Flexibility is seen as a desirable attribute of a manufacturing system. Virtually every manufacturing organisation wants it, but find it difficult to define, predict or measure. Most researchers look inwards to try to obtain measures. This research defines a framework that provides a structured methodology for developing flexibility requirements. The framework ensures that the flexibility requirements are derived from manufacturing objectives that relate to business strategy. This way flexibility becomes an issue that is driven by the business needs and not just by the advances in technology. Through the framework all the important factors of the business as a whole are considered in the design of the manufacturing system. The research examines the tactical level of decision making in detail. A simulation model was developed to predict the performance of a manufacturing system faced with various types of flexibility requirements. The model was used to convert potential flexibility to demonstrated flexibility, thereby predicting the manner in which the manufacturing system might perform. The results from the model showed the performance of the whole system and these were related to the contribution that flexibility makes to the overall manufacturing objectives. However, it was also observed that different types of models may be required depending on the nature of the decisions. Through the development of the mechanism for evaluating flexibility requirements, it was observed that much time was invested in the definition of flexibility requirements and how these contributed to the manufacturing strategy. This shows that much time needs to be spent on the definition of flexibility requirements before evaluation can take place.